Welfare participation by immigrants in the UK - Stephen Drinkwater; Catherine Robinson (Institute for the Study of Labor (IZA), 2011)
Welfare participation is an important indicator of how successfully immigrants perform in the host country. This paper examines this issue for the UK, which has experienced a large growth in its immigrant flows and population levels in recent years, especially following EU enlargement in 2004. The analysis focuses in particular on the types of benefits that immigrants tend to claim as well as examining differences by area of origin. It also examines the factors that determine social benefit claims, including an investigation of the impact of education, ethnicity and years since migration. Social welfare claims vary considerably by immigrant group as well as by the type of benefit claimed in the UK. There is also some variation by gender within the migrant groups.
urn:nbn:de:101:1-2012010913646
Keywords: J61; F22; I38; 330; immigration; United Kingdom; benefit claims; EU enlargement